2013
DOI: 10.1007/s11414-013-9323-5
|View full text |Cite|
|
Sign up to set email alerts
|

Hospital Readmission Among Medicaid Patients with an Index Hospitalization for Mental and/or Substance Use Disorder

Abstract: Hospital readmission rates are increasingly used as a performance indicator. Whether they are a valid, reliable, and actionable measure for behavioral health is unknown. Using the MarketScan Multistate Medicaid Claims Database, this study examined hospital- and patient-level predictors of behavioral health readmission rates. Among hospitals with at least 25 annual admissions, the median behavioral health readmission rate was 11% (10th percentile, 3%; 90th percentile, 18%). Increased follow-up at community ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 16 publications
7
53
2
Order By: Relevance
“…A recent study examined readmission rates for mental health and/or substance use disorder among a national sample of Medicaid enrollees from 2004-2009. Among 121,271 discharges, they found that 46% had any follow-up in 7 days, but only 7.4 % and 11.4% had follow-up with a psychiatrist or community mental health center respectively [29]. Although these results represent a broader population group and are not directly comparable to our findings, they similarly reflect lower rates of follow-up with primary care and mental health providers post hospital discharge.…”
Section: Discussioncontrasting
confidence: 61%
“…A recent study examined readmission rates for mental health and/or substance use disorder among a national sample of Medicaid enrollees from 2004-2009. Among 121,271 discharges, they found that 46% had any follow-up in 7 days, but only 7.4 % and 11.4% had follow-up with a psychiatrist or community mental health center respectively [29]. Although these results represent a broader population group and are not directly comparable to our findings, they similarly reflect lower rates of follow-up with primary care and mental health providers post hospital discharge.…”
Section: Discussioncontrasting
confidence: 61%
“…They can further be divided into studies capturing potential hospital size effects [1417], capacity variables [1823], resource availability/utilisation/ quality [14, 17, 24, 25], length of stay [14, 1618, 20], case-mix [14, 20], treatment policies or orientation [14, 16, 17, 26], hospital type [24, 25, 27, 28] and community aftercare [14, 16, 17, 29–36]. …”
Section: Resultsmentioning
confidence: 99%
“…Hospital length of stay is consistently found to be negatively related to (risk/rate of) readmission when measured both at hospital level or community level [14, 1618, 20]. Heggestad [24] also found that high patient turnover (annual discharges/beds) increased the likelihood of readmissions.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have documented the link between substance use diagnoses and hospitalization or readmission in Medicaid 14,15,17 and in smaller samples, 30 and the link between those diagnoses and admissions nationally known to be directly related to drug use. 22,23 Our study extends the literature by examining hospitalizations across relatively nuanced substance use profiles in a large nationally representative sample.…”
Section: Discussionmentioning
confidence: 99%